Respuesta :
Answer:
Final answer is [tex]\frac{157}{15} [/tex]
Step-by-step explanation:
Given expression is
[tex]\frac{4}{5} +6-\frac{3}{9} +4[/tex]
Now we need to simplify that.
[tex]\frac{4}{5} +6-\frac{3}{9} +4[/tex]
[tex]=\frac{4}{5}+6-\frac{1}{3}+4 [/tex]
[tex]=\frac{4}{5}-\frac{1}{3}+10 [/tex]
[tex]=\frac{4}{5}\cdot\frac{3}{3}-\frac{1}{3}\cdot\frac{5}{5}+10\cdot\frac{15}{15} [/tex]
[tex]=\frac{12}{15}-\frac{5}{15}+\frac{150}{15} [/tex]
[tex]=\frac{12-5+150}{15} [/tex]
[tex]=\frac{7+150}{15} [/tex]
[tex]=\frac{157}{15} [/tex]
Hence final answer is [tex]\frac{157}{15} [/tex]
Answer:
157/150
Step-by-step explanation:
We have given :
4/5+6-3/9+4
We have to simplify this expression.
4/5+6-3/9+4 = 4/5-1/3+10
The LCM of this expression is 15.
Multiply each term by 15 we get,
(12-5+150)/15
(7-150)/15
157/150 is the simplification.